Protease recognition sites in Bet v 1a are cryptic, explaining its slow processing relevant to its allergenicity - Freier, Regina (Sci Rep, 2015)
Despite a high similarity with homologous protein families, only few proteins trigger an allergic immune response with characteristic T(H)2 polarization. This puzzling observation is illustrated by the major birch pollen allergen Bet v 1a and its hypoallergenic protein isoforms, e.g., Bet v 1d. Given the key role of proteolytic processing in antigen presentation and T cell polarization, we investigated the recognition of Bet v 1 isoforms by the relevant protease cathepsin S. We found that at moderately acidic pH values Bet v 1a bound to cathepsin S with significantly lower affinity and was more slowly cleaved than its hypoallergenic isoform Bet v 1d. Only at pH values ≤4.5 the known proteolytic cleavage sites in Bet v 1a became accessible, resulting in a strong increase in affinity towards cathepsin S. Antigen processing and class II MHC loading occurs at moderately acidic compartments where processing of Bet v 1a and Bet v 1d differs distinctly. This difference translates into low and high density class II MHC loading and subsequently in T(H)2 and T(H)1 polarization, respectively.